The effects of within stand disturbance in plantation forests indicate complex and contrasting responses among and within beetle families - Mladenović, S; Loskotová, T; Boháč, J; Pavlíček, J; Brestovanský, J; Horák, J (Bulletin of entomological research, 2018)
Plantation forests with timber production as the major function are highly fragmented and disturbed regarding the tree species composition and stand area. Their closed canopies also have different microclimatic conditions compared with better studied conservation areas. We studied three beetle families (click, longhorn, and rove beetles) with different ecological demands in lowland plantation forests dominated by Sessile oak and Norway spruce in the Czech Republic. Our main interest was how their species richness, abundance, diversity, body length, rarity, red-list status, species composition and individual species were driven by the main tree species, stand area and canopy openness. We analyzed 3466 individuals from 198 beetle species and the results revealed complex and contrasting responses of the studied beetle families - click beetles mostly preferred sun-exposure and spruce as the dominant tree species, longhorn beetles mainly preferred large stands, whereas rove beetles were mostly influenced by oak as the dominant tree species and increasing area. We also observed that some species had different preferences in plantation forests than is known from the literature. The main conclusions of our results are that the dominance of non-natural spruce plantations and a large stand area (both originating from artificially replanted large clear-cuts) did not affect the majority of the studied taxa as we expected. On the other hand, our results might have been influenced by other factor, such as the current small total area of the former vegetation, which in the past might have led to extinction debt; or a large area of other conifers in the surroundings that might have promoted conifer-associated fauna.
Keywords: brouci; lesnictví; Conservation of Natural Resources; Česká republika; společenstvo; Microclimate; Forestry; stand area; Czech Republic; mikroklima; Norway spruce; zachování přírodních zdrojů; zvířata; biodiversity; Coleoptera; populační dynamika; canopy openness; lesy; forest ecology; Biota; Sessile oak; Population Dynamics; Forests; Animals